2020
DOI: 10.3348/kjr.2019.0831
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Ultrasound: A Pictorial Essay

Abstract: Most patients with nipple pathologies typically present with the associated symptoms upon clinical examination (3). The magnifying lamp is a useful tool to inspect nipple

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Due to the low incidence of NA, literature about its ultrasonographic findings only includes case reports. Ultrasonographic findings can be described as hypoechoic nodules with a clear inner boundary, enhanced posterior echo, and uniform internal echo, which are round or oval in shape, and which have a small amount of blood flow or marginal blood flow inside (15,16). In our study, 22 cases of NA were examined by ultrasound.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Due to the low incidence of NA, literature about its ultrasonographic findings only includes case reports. Ultrasonographic findings can be described as hypoechoic nodules with a clear inner boundary, enhanced posterior echo, and uniform internal echo, which are round or oval in shape, and which have a small amount of blood flow or marginal blood flow inside (15,16). In our study, 22 cases of NA were examined by ultrasound.…”
Section: Discussionmentioning
confidence: 93%
“…However, not all breast lesions can be detected by ultrasound. Some studies have shown that 13% of patients with PD cannot be detected by ultrasound or X-ray (16). MRI plays an important role in the preoperative examination of nipple areola lesions, especially in patients with negative breast X-ray and ultrasound results.…”
Section: Discussionmentioning
confidence: 99%
“…It is a benign, asymptomatic mesenchymal tumor that rarely exceeds 2 cm. This tumor develops more in certain areas such as the face, neck, armpit and groin [1]. Although it is a common lesion, the nipple is an unusual site for it [2].…”
Section: Introductionmentioning
confidence: 99%